Lattice phenomenology of minimal walking technicolor - Kerrane, Eoin (The University of Edinburgh, 2012)
As results from the Large Hadron Collider (LHC) begin to shed light on the physics of the electroweak scale, which has been of primary interest to theorists for many years, we have entered a phase where critical judgement of the many models of electroweak symmetry breaking (EWSB) that have been developed in recent years will be possible. As this process continues, those models which are not additionally constrained by emerging data attract increased scrutiny and interest. In this respect, technicolor models, in which EWSB occurs dynamically through the spontaneous chiral symmetry breaking in a new strongly coupled sector, are the subject of growing research activity. The focus of this work is a program of investigation of Minimal Walking Technicolor (MWT), a candidate theory for the new strongly coupled sector of a model of dynamical EWSB using Lattice Gauge Theory (LGT) techniques. We have performed an improved comprehensive study of mesonic spectral observables within MWT, with emphasis on nite volume e ects arising from nite temporal and spatial boundaries. Our results clarify the role of nite volume e ects in such studies, while con rming the near-conformal behaviour of the theory in the infra-red, and indicating a relatively small value of the mass anomalous dimension, in agreement with other studies. We also describe a calculation of the leading order hadronic vacuum polarisation contribution to the anomalous magnetic moment of the muon from a lattice simulation of 2+1 avour lattice QCD using Domain Wall Fermions (DWF). We investigate in detail a number of systematic uncertainties involved in this calculation, determining how to e ectively bring them under control, and obtain a result in close agreement with previous determinations from LGT studies, from calculations based on independent experimental data, and from experimental measurements. We present a preliminary calculation of the contribution to the electroweak S parameter from MWT, using a mixed-action simulation involving the DWF action used for the valence sector combined with gauge con gurations generated using the Wilson fermion action for sea quarks.
Keywords: lattice; technicolor